The Environment of Reality: An Experiment in Education for Business. - Graham, Curtis C.; Manship, Darwin W. (The Accounting Review, 1973)
The article presents information on a business course initiated on an experimental basis at Boise State College. The educational syndrome afflicts a great many junior and senior students. This affliction is characterized by a lack of enthusiasm for course materials, a failure to integrate the various disciplines into a meaningful knowledge base, a concentration on achieving high grades rather than high levels of understanding, and a grudging tolerance of business disciplines which are not a part of the student's major field of interest. The basis for the course is a legally chartered non-profit, tax-exempt corporation licensed to conduct a variety of business activities. The corporation's board of directors consists of six student members and three administration representatives. Grades for the course are recommended by the students and are based on a standard evaluation form which is filled out by each student supervisor. In turn, the supervisors are evaluated by their respective subordinates. These recommended grades are submitted to the class instructor who makes the final determination.